Evaluation of an online interprofessional course on ethics and professionalism: experience of medical, dental, and pharmacy students - Atwa, Hani; Farghaly, Amira; Badawi, Jude Tareq; Malik, Louay Fadi; Abdelnasser, Asmaa (Frontiers in Education, 2024)
Ethics and professionalism in the health professions reflect how health professionals behave during practice, based on their professional values and, attitudes and behaviors. Health professions education institutions have implemented various strategies for teaching ethics and professionalism, including interprofessional education. The aim of the study was to evaluate the perception of undergraduate health professions students about the outcomes of an online interprofessional course in ethics and professionalism as well as their perception of interprofessional education and the importance of ethics and professionalism after taking the course. This is a descriptive crosssectional study that targeted medical, dentistry, and pharmacy students. A researcher-made 31-item questionnaire was used. The questionnaire was tested for face, content, and construct validity.Reliability of the questionnaire was estimated by Cronbach alpha test. Descriptive statistics were used. T-test was performed to compare the results of male and female students and ANOVA was performed to compare the results of medical, dentistry, and pharmacy students. Statistical significance was set at p < 0.05. Factor analysis of the questionnaire yielded three factors, namely course evaluation, perception of interprofessional education, and importance of ethics and professionalism in health professions education. The study participants expressed positive perceptions of all aspects of the course. They reported positive perceptions of interprofessional education, highlighting its benefits in enhancing understanding, teamwork skills, and respect for other healthcare professionals. The findings reveal some program-related differences in participants' responses, where medical students showed higher ratings of all aspects of the course, interprofessional education and importance of ethics and professionalism. Students of the three programs showed positive perceptions of the online IPE course on ethics and professionalism as well as the benefits of IPE and the importance of ethics and professionalism. This highlights the effectiveness of the course in addressing such important aspects of health professions education.